Allantoin improves methionine-choline deficient diet-induced nonalcoholic steatohepatitis in mice through involvement in endoplasmic reticulum stress and hepatocytes apoptosis-related genes expressions - Tahereh Komeili Movahhed; Azam Moslehi; Mohammad Golchoob; shima ababzadeh (Iranian Journal of Basic Medical Sciences, 2019)
Objective(s): Non-alcoholic steatohepatitis (NASH) is defined by steatosis and inflammation in the hepatocytes, which can progress to cirrhosis and possibly hepatocellular carcinoma. However, current treatments are not entirely effective. Allantoin is one of the principal compounds in many plants and an imidazoline I receptor agonist as well. Allantoin has positive effects on glucose metabolism and inflammation. In this study, the effects of allantoin on the NASH induced animals and the pathways involved have been evaluated. Materials and Methods: C57/BL6 male mice received saline and allantoin as the control groups. In the next group, NASH was induced by the methionine-choline-deficient diet (MCD) for eight weeks. In the NASH+allantoin group, allantoin was injected four weeks in the mice feeding on an MCD diet. Histopathological evaluations, serum analysis, ELISA assay, and real-time RT-PCR were performed. Results: Allantoin administration decreased serum alanine aminotransferase (ALT), cholesterol, low-density lipoprotein (LDL), hepatic lipid accumulation, and liver tumor necrosis factor (TNFα) level. Also, treatment with allantoin down-regulated the gene expression of glucose-regulated protein 78 (GRP78), activating transcription factor 6 (AFT6), TNFα, sterol regulatory element binding proteins 1c (SREBP1c), fatty acid synthase (FAS), Bax/Bcl2 ratio, caspase3, and P53. On the other hand, peroxisome proliferator-activated receptor alpha (PPARα), apolipoprotein B (Apo B), and acetyl-coenzyme acetyltransferase 1 (ACAT1) gene expression increased after allantoin injection. Conclusion: This study indicated that allantoin could improve animal induced NASH by changes in the expression of endoplasmic reticulum stress-related genes and apoptotic pathways.